Immunosuppressive drug withdrawal late after liver transplantation improves the lipid profile and reduces infections. Issue 11 (November 2019) - Duizendstra, Aafke A.; de Knegt, Robert J.; Betjes, Michiel G.H.; Coenen, Sandra; Murad, Sarwa Darwish; de Man, Rob A.; Metselaar, Herold J.; Sprengers, Dave; Litjens, Nicolle H.R.; Kwekkeboom, Jaap
Abstract : Background: Treatment with immunosuppressive drugs (IS) after transplantation is accompanied by severe side effects. A limited number of studies have investigated the effect of IS withdrawal on IS-related comorbidities after liver transplantation (LTx) and the results are contradictory. Patients and methods: We determined in a retrospective case–control study the clinical effects of complete IS withdrawal in operationally tolerant (TOL) LTx recipients who discontinued IS 10.8 ± 5.1 years after LTx ( n = 13) compared with a completely matched control (CTRL) group with a regular IS regimen ( n = 22). TOL recipients have been IS and rejection free for 4.0 ± 2.8 years. Results: IS withdrawal in TOL recipients resulted in lower low-density lipoprotein levels ( P = 0.027), whereas this was not observed in the CTRL group. Furthermore, persistent infections in individual recipients were resolved successfully by IS withdrawal. TOL recipients also had significantly fewer de novo infections after IS withdrawal (TOL pre vs. post withdrawal P = 0.0247) compared with recipients continued on IS during the same follow-up period (post withdrawal TOL vs. CTRL P = 0.044). Unfortunately, no improvement in kidney function, and lower rates of de novo occurrences of diabetes, hypertension, cardiovascular diseases, and malignancies were observed in the TOL group after IS withdrawal compared with the CTRL group during the same follow-up time period. Conclusion: IS withdrawal late after LTx reduces infection rates and low-density lipoprotein levels, but other IS-related side effects persist late after LTx. An accurate tolerance immune profile enabling identification of tolerant LTx recipients eligible for safe IS withdrawal earlier after transplantation is needed to prevent the development of irreversible IS-related side effects. Abstract : Supplemental Digital Content is available in the text.